Effect of supplementation with ruminal probiotics on growth performance, carcass characteristics, plasma metabolites, methane emissions, and the associated rumen microbiome changes in beef cattle. (3rd January 2023) - Pittaluga, Alejandro M; Yang, Fan; Gaffney, James R; Embree, Mallory; Relling, Alejandro E
Abstract: To evaluate the effect of supplementing beef cattle with a ruminal probiotic consisting of native rumen microbes (NRM; Chordicoccus furentiruminis, Prevotella albensis, and Succinivibrio dextrinosolvens ) on methane (CH4 ) emissions, growth performance, carcass characteristics, and plasma metabolites, Angus × SimAngus-crossbred steers ( n = 32; 8 per pen) and heifers ( n = 48; 12 per pen) with an initial body weight (BW) of 353 ± 64 kg were used in randomized complete block design. Cattle were blocked by sex and BW and randomly assigned to 1 of 2 treatments (2 pens per treatment). Treatments consisted of diets offered for ad libitum intake with (NRM) or without (CON) the inclusion of the ruminal probiotic. Cattle were fed a growing diet for 49 d followed by a ground corn-based diet for 124 ± 27 d until reaching the targeted final BW (635 kg for steers and 590 kg for heifers). Methane emissions were estimated using the GreenFeed system ( n = 12 per treatment) prior to trial commencement (baseline; period 1), and on three (2, 3, and 4), and two (5 and 6) different sampling periods throughout the growing and finishing stage, respectively. All data were analyzed using the PROC MIXED procedure of SAS. For CH4 production (g/d), there was a tendency for an NRM supplementation × period interaction ( P = 0.07) where cattle-fed diets with NRM had lower production of methane in periods 3 and 4. Including NRM in the diet decreased CH4 yield (g/kg of dry matter intake (DMI)) by 20%. For CH4 emission intensity (g/kg of average daily gain (ADG)), an interaction ( P < 0.01) of NRM supplementation × period occurred. In periods 2 and 3, cattle-fed diets with NRM inclusion had lower CH4 emission intensity than CON cattle. During the 84-d period when all cattle were still on the finishing diet, feeding NRM increased ( P = 0.02) ADG and tended to increase ( P = 0.10) DMI. At the end of the 84-d period, cattle-fed NRM tended to be heavier ( P = 0.06) than CON cattle. Cattle supplemented with NRM required less ( P = 0.04) days on feed to reach the targeted final BW. No differences ( P ≤ 0.11) were detected for gain-to-feed ratio and carcass characteristics. Cattle-fed NRM had greater abundance of uncultured rumen bacteria that may improve rumen digestion when fed a high grain diet and potentially promote the reduction of enteric CH4 production. Results from this study suggest that daily administration of NRM may be a strategy to mitigate methanogenesis and improve the growth performance of beef cattle. Abstract : Alternatives to effectively mitigate methane emissions of beef cattle are needed. This experiment investigated the dietary inclusion of ruminal probiotics as a potential anti-methanogenic feed additive and its effect on the growth performance of beef cattle. Lay Summary: Greenhouse gas emissions are a major concern in the beef industry. This study examined the effects of supplementation with ruminal probiotics consisting of three native ruminal microbes (NRM) for their influence on methane reduction and growth performance of beef cattle. Eighty Angus × SimAngus-crossbred cattle were grouped by sex and weight, randomly assigned to a treatment group, control or NRM supplementation, and subsequently fed commercially relevant diets for at least 134 d with or without NRM supplementation until they reached a target finishing weight. Methane emissions and growth performance metrics were recorded at regular intervals. Cattle-fed diets with NRM had a greater average daily gain during most part of the experimental period, required fewer days to reach the finishing weight, and emitted less methane than cattle in the control treatment. Supplementing NRM can be a viable method to reduce greenhouse gas emissions while improving the performance of beef cattle-fed concentrates-based diets.